PERAN FILSAFAT DALAM PENGEMBANGAN TEORI PENDIDIKAN THE ROLE OF PHILOSOPHY IN THE DEVELOPMENT OF EDUCATIONAL THEORY - Asep Idin Asep; Siti Fadjarajani Siti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The relationship between philosophy and educational theory has always been an intriguing subject, especially for those who delve deeply into educational studies. To explore the vast field of educational theory, philosophy plays a key role in helping educators and thinkers develop and understand educational theories. This paper, through a literature review, aims to explore the connection between philosophy and educational theory, drawing on various theoretical approaches and findings from prAevious authors. Philosophy influences the development of other fields of knowledge, and this forms the horizontal relationship between philosophy, including philosophy of education, and other branches of knowledge. In a vertical sense, philosophy of education is connected to other fields, such as educational science and the history of education. The results of this study conclude that philosophy's role in educational theory provides a profound contribution to discovering the truth in educational theories, thus making education not only a scientific discipline but also offering practical benefits in its implementation.